Determination of Physicochemical Properties of Wastewater from the Petrochemical Industry - Brownson, David Nekabari; Nwandu, Lilian Nneka (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
Industrial wastewater has been a significant source of environmental pollution for quite a long time. Therefore, it is very essential to make sure that the wastewater discharged from a petrochemical plant meets the regulations set by the authorities. To confirm this fact, a study was performed as a reaction to the issues raised by determining the physicochemical parameters of the water samples taken from different locations and comparing their levels with those of the World Health Organization (WHO) standards and specifications. The standards have been adopted for all the tested parameters. Three of the measured parameters: pH, electrical conductivity (EC), and turbidity had values that were within the intervals of 7.3 – 8.2, 741 – 1297 µS/cm, and 26 – 71 NTU, respectively. The rest of the variables had ranges as follows: total dissolved solids (TDS, 401 – 619 mg/L); total suspended solids (TSS, 20–40 mg/L); dissolved oxygen (DO, 47–60 mg/L); chemical oxygen demand (COD; 87–130 mg/L); oil and grease (O&G, 2–10 mg/L); biochemical oxygen demand (BOD, 12–20 mg/L).